2002
DOI: 10.1046/j.1524-4725.2002.02091.x
|View full text |Cite
|
Sign up to set email alerts
|

Nonablative Laser Skin Resurfacing using a 1540 nm Erbium Glass Laser: A Clinical and Histologic Analysis

Abstract: The nonablative 1540 nm erbium glass laser system with contact cooling produces gradual clinical and histologic improvement in mild to moderate facial rhytides with minimal risk of serious adverse sequelae.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
73
0

Year Published

2004
2004
2010
2010

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 99 publications
(74 citation statements)
references
References 30 publications
1
73
0
Order By: Relevance
“…The selective thermal damage of the dermis is followed by a wound healing response from the damaged tissue, which ultimately leads to new collagen formation. The absence of epidermal damage decreases the severity and degree of side effects that are associated with the treatment [10][11][12][13][14][15]. Although most studies have indicated significant levels of patient satisfaction and even histological and biochemical evidence of improvement, photographic assessment by blinded observers has often found only minimal or no improvement.…”
Section: Discussionmentioning
confidence: 99%
“…The selective thermal damage of the dermis is followed by a wound healing response from the damaged tissue, which ultimately leads to new collagen formation. The absence of epidermal damage decreases the severity and degree of side effects that are associated with the treatment [10][11][12][13][14][15]. Although most studies have indicated significant levels of patient satisfaction and even histological and biochemical evidence of improvement, photographic assessment by blinded observers has often found only minimal or no improvement.…”
Section: Discussionmentioning
confidence: 99%
“…Some reports demonstrate that the 1540-nm laser has reduced acne lesions with good tolerability [22,23].…”
Section: Laser Therapymentioning
confidence: 99%
“…In one study, 18 the 1540-nm erbium glass laser produced mild-tomoderate clinical improvement in the periorbital and perioral regions. The periorbital region with the thinnest skin was the most responsive.…”
Section: More Recent Nonablative Lasersmentioning
confidence: 99%
“…11 Currently, technology used for nonablative skin rejuvenation includes the CoolTouch laser (CoolTouch Inc, Roseville, Calif), [12][13][14] Visage radiofrequency (ArthroCare Corp, Sunnyvale, Calif), 15,16 the DioLite Laser (Iridex Corp, Mountain View, Calif), 17 1540-nm erbium glass laser, 18 and intense pulsed-light sources. 19,20 More recently, the 1450-nm SmoothBeam laser (Candela Laser Corp, Wayland, Mass) has also become available for nonablative collagen stimulation.…”
Section: Introductionmentioning
confidence: 99%